Diagnostic ability of Japan Narrow-Band Imaging Expert Team classification for colorectal lesions by magnifying endoscopy with blue laser imaging versus narrow-band imaging - Ito, Renma; Ikematsu, Hiroaki; Murano, Tatsuro; Shinmura, Kensuke; Kojima, Motohiro; Kumahara, Kana; Furue, Yasuaki; Sunakawa, Hironori; Minamide, Tatsunori; Sato, Daiki; Yamamoto, Yoichi; Takashima, Kenji; Yoda, Yusuke; Hori, Keisuke; Yano, Tomonori (Endoscopy International Open, 2021)
Background and study aims The Japan Narrow-band imaging (NBI) Expert Team (JNET) classification was proposed for evaluating colorectal lesions. However, it remains unknown whether the JNET classification can be applied to magnifying endoscopy with image-enhanced endoscopies other than NBI. This study aimed to compare the diagnostic ability of JNET classification by magnifying endoscopy with blue laser imaging (ME-BLI) and with ME-NBI.Patients and methods We retrospectively assessed consecutive patients diagnosed per the JNET classification by ME-BLI (BLI group) or ME-NBI (NBI group) between March 2014 and June 2017. We compared the diagnostic value of JNET classification between the groups with one-to-one propensity score matching. Results Four hundred and seventy-one propensity score-matched pairs of lesions were analyzed. In the BLI and NBI groups, the overall diagnostic accuracies were 92.1 % and 91.7 %, respectively, and those for differentiating between neoplastic and non-neoplastic polyps were 96.6 % and 96.8 %, respectively. The positive predictive value by each JNET classification in BLI vs. NBI group was 90.6 % vs. 96.2 % in Type 1, 94.3 % vs. 94.6 % in Type 2A, 57.7 % vs. 42.3 % in Type 2B, and 100 % vs. 91.7 % in Type 3. The negative predictive value was 97.0 % vs. 96.9 % in Type 1, 88.1 % vs. 82.8 % in Type 2A, 98.0 % vs. 98.2 % in Type 2B, and 98.5 % vs. 98.7 % in Type 3. No statistical difference in the diagnostic results was found between the groups. Conclusions The diagnostic ability of the JNET classification by ME-BLI and ME-NBI was comparable, with the former also applicable for diagnosis of colorectal lesions.